Family Communication As A Foundation Of Mental Health: Roles And Responsibilities - Fayyadh Fadhlurrohman Assegap; Faiz Abdul Haq; Siti Khumayah; Dedet Erawati (Syntax Corporation Indonesia, 2025)
The family serves as the primary foundation for shaping individual behavior, values, and mental health. A warm, supportive, and communicative family environment can provide a strong basis for the psychological well-being of each member. Conversely, conditions such as conflict, neglect, and poor communication may trigger mental health issues, particularly among adolescents. In the current era, especially for Generation Z, mental health has become a critical issue, yet it is often overlooked by some parents. Adolescents who do not receive sufficient attention and emotional support from their families are more likely to experience psychological problems, including anxiety, depression, and difficulties in adaptation. This study aims to identify the roles and responsibilities of the family in supporting children's mental health, with a focus on communication patterns, emotional closeness, and cultural values that shape the dynamics of family relationships. Through a qualitative approach, this research explores how families can serve as vital agents in the prevention of mental disorders and the development of psychological resilience in adolescents.